Drylot Backgrounding of Beef - Jones, Rodney D. (My University, 2007)
This publication helps producers that have a drylot backgrounding enterprise, and uses projected input and output prices for illustrative purposes to find the break-even price.
MF600_2007_10
Keywords: MF600; Economics; Livestock; MF